PELUANG DAN TANTANGAN EKSPOR IMPOR DI ERA GLOBALISASI - Saputri, Luluk; Hamidah, Selvi Wildatul; Husna, Nayla Syafaatal (Jurnal Ekonomi Sakti, 2024)
The era of globalization has brought significant changes in the dynamics of international trade, providing various opportunities and challenges in import-export activities. Globalization creates more open and integrated markets, and allows countries to exchange goods and services more efficiently. The Word Trade Organization (WTO) established after the Uruguay Round in Marrakesh, Morocco marks a new era in international trade, where the WTO plays an important role in regulating and encouraging free trade between member countries. This study uses descriptive qualitative research methods to explore the opportunities and challenges of exports and imports in the era of globalization. Through this research, it was found that globalization facilitates access to international markets, technological innovation and understanding of global markets, all of which contribute to increasing economic growth. On the other hand, countries and businesses must face challenges such as intense global competition, changing consumer tastes, and rapid technological development. To face these challenges, countries, especially developing countries, must implement effective and open international policies, such as export promotion, import substitution, and industrial protection. At the same time, the development of technology and logistics infrastructure also plays an important role in accelerating the international trade process, allowing businesses to access a wider market at a lower cost. Keywords: export; import; globalization; international trade